KADAR MINYAK DAN KERNEL PADA BUAH TERLUAR SELAMA PEMATANGAN TANDAN BUAH KELAPA SAWIT - Hasrul Abdi Hasibuan (Pusat Penelitian Kelapa Sawit, 2020)
This study aims to determine the composition of oil and kernel in the outer oil palm fruit during ripening of bunches from the Tenera oil palm species. The activities was carried out include: i) observation of loose fruit of bunches including the amount, weight, oil and kernel content, ii) observation of the effect of staying overnight in open and shaded spots (under palm trees) on the weight, oil content and kernel and iii) analysis of oil and kernel composition on variations in fruit maturity on lowland, highland and peat land. The results obtained from the first activity were loose fruit on the first day of 1-2 grains per bunch (average 1.3 ± 0.5 grains / bunch) and the number increased on the second up to sixth day as much as 3.2 ± 0.8 grains / bunches. Loose fruit on the first and second day tend to be heavier than the day after. Loose fruit on the first day has higher oil content than the day after. The oil content in dry mesocarp increased with increasing time of fruit release while the kernel content was same relatively. The results obtained from the second activity were the loose fruit weight decreased during staying overnight in the open space (days 1-10 by 4.8-27.1%) higher than in the shade (2.1-17.2%). The oil content on loose fruit increased with increasing of staying overnight time. During the tenth day, the oil content of the loose fruit placed in the open spot increased significantly and differed significantly at the level of p≤0.05 compared to the previous time due to the weight of the loose fruit decreased significantly. Meanwhile, kernel content per fruit during lodging was not significantly different until the tenth day in both places. The results obtained from the third activity were the oil content increased in unripe to overripe fruit and not differed significantly at the 5% level in ripe and overripe. The kernel content increased but not differed significantly at the level of 5% in unripe to overripe fruit. The water content of unripe fruit decreased with increasing fruit maturity. The oil content of fruit in the lowland was higher than the highland and peat land. Fruit has oil and kernel content optimum was the fruit that has loose fruit a minimum of 1 grain per bunches.